2010
DOI: 10.1021/bi1011942
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Base Analogues within a CpG Dinucleotide on the Binding of DNA by the Methyl-Binding Domain of MeCP2 and Methylation by DNMT1

Abstract: The epigenetic control of transcription requires the selective recognition of methylated CpG dinucleotides by methylation-sensitive sequence-specific DNA binding proteins. In order to probe the mechanism of selective interaction of the methyl-binding protein with methylated DNA, we have prepared a series of oligonucleotides containing modified purines and pyrimidines at the recognition site, and we have examined the binding of these oligonucleotides to the methyl-binding domain (MBD) of the methyl-CpG-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…We verified this by conducting equilibrium competitive binding assays and comparing the relative affinities of the MeCP2 MBD for these 28-bp quasi-specific DNA duplexes (Figure 3B ). The affinity of the MeCP2 MBD for the methylated DNA (the dissociation constant K d = 2.3 nM) was 54-fold higher than that for the unmethylated DNA ( K d = 124 nM), which is consistent with a previous study ( 42 ).…”
Section: Resultssupporting
confidence: 92%
“…We verified this by conducting equilibrium competitive binding assays and comparing the relative affinities of the MeCP2 MBD for these 28-bp quasi-specific DNA duplexes (Figure 3B ). The affinity of the MeCP2 MBD for the methylated DNA (the dissociation constant K d = 2.3 nM) was 54-fold higher than that for the unmethylated DNA ( K d = 124 nM), which is consistent with a previous study ( 42 ).…”
Section: Resultssupporting
confidence: 92%
“…Active DNA demethylation is currently thought of as being a stepwise process - hydroxylation of 5mC (5hmC) by TET proteins followed by deamination by AID/APOBEC protein or carboxylation and entry in to the subsequent base excision repair (BER) pathway(Bhutani et al, 2011). Alternatively, 5hmC is not recognized by DNMT1(Lao et al, 2010), replication of DNA containing this base would lead to loss of the 5mC mark in the subsequent S phase.…”
Section: How Genetics Affect Epigeneticsmentioning
confidence: 99%
“…MBPs may also recruit transcriptional co-repressor molecules [132] , [133] , [134] , [135] . A series of studies by Dr. Sowers’ group documented that the recognition elements of MBPs include the guanine's O6 and N7 atoms present in the major groove [136] , and the oxidation of guanine converts the N7 position from a hydrogen bond acceptor to a hydrogen bond donor and replaces the 8-proton with an oxygen atom, potentially interfering with the recognition of the methyl-CpG dinucleotide by MBPs [137] . EMSAs revealed that the oxidation of guanine to 8-oxoG significantly inhibits binding of the methyl-CpG-binding domain of methyl-CpG-binding protein 2 (MeCP2) to the oligonucleotide duplex [137] .…”
Section: Epigenetic Role Of Guanine Oxidation In Gene Expressionmentioning
confidence: 99%